?SPECTROPHOTOMETRIC DETERMINATION OF PA-LLADIUM (II) WITH RUBEANIC ACID (RA) IN PRESENCE OF PYRIDINE, PIPERIDINE AND 3-PICOLINE (Biological Sciences - PJSIR, 1999)
Unpretentious and exclusive methods for the spectrophotometric determination of trace amount of divalent palladium (II) have been developed with rubeanic acid (dithio-oxamide) in presence of secondary iigands like pyridine, piperidine and 3-picoline. Both direct and extraction spectrophotometry showed that coloured rubeanates are only stable in acidic medium. The violent yellow coloured products are formed below pH 5.0 with an absorption maxima at 416.0 and 422.0 (pyridine), 405.0 and 416.5 (piperidine) and 418.0 and 422.0 (3-picoiine) both in direct and isoamyl alcohol (IAA) extracted system, respectively. Results indicate that the highest sensitivity and molar absorptivity of Pd-RA pyridine system in direct spectrophotometry were 0.01497 ug Pd (II) em? and 7\07.89 L mol' cm' respectively. IAA extracted Pd-RA-piperidine system was found to give a sensitivity of 0.0\087 ~g(Pd(II) crrr? and molar absorptivity of 9788.80 L mol:' em:' which were the highest of all the system. The effects due to variation of pH, reagent concentrations, order of addition of reagents, time, temperature and solvent media on the absorption spectra have been investigated and the optimum conditions determined. The effects of diverse ions and their tolerance limit have also been studied .